Low thermal conductivity in high-entropy rare-earth pyrosilicate solid-solutions for thermal environmental barrier coatings. (15th January 2021) - Turcer, Laura R.; Sengupta, Arundhati; Padture, Nitin P.
Abstract: Dense thermal environmental barrier coatings (TEBCs) with low thermal conductivities are needed for the protection and insulation of SiC-based ceramic matrix composites (CMCs) in future gas-turbine engines. Here we demonstrate experimentally that the high-temperature thermal conductivity of dense β-Yb2 Si2 O7 pyrosilicate ceramic can be reduced progressively in β-(Y0.1 Yb0.9 )2 Si2 O7 and β-(Y0.5 Yb0.5 )2 Si2 O7 solid-solutions for TEBC application. We also demonstrate that by going to a dense five-component equi-atomic single-phase β-(Y0.2 Yb0.2 Sc0.2 Gd0.2 Lu0.2 )2 Si2 O7 pyrosilicate high-entropy ceramic (HEC), the thermal conductivity can be reduced further to 1.52 W.m.K −1 (at 1000 °C). This is attributed to enhanced phonon scattering due to the increased mass-disorder with the incorporation of the additional RE 3+ cations in the HEC. Although the high-entropy aspect and bonding-disorder do not appear to contribute significantly to the phase stability or the low thermal conductivity in such HECs, they are strong candidates for future TEBCs for CMCs. Graphical abstract: Image, graphical abstract